Partial external mitral annuloplasty in dogs with myxomatous mitral valve degeneration and congestive heart failure: Outcome in 9 cases - De Andrade, James N.B.M.; Christopher Orton, E.; Boon, June; Nishimori, Celina T.D.; Olivaes, Claudio; Camacho, Aparecido A. [UNESP] (Elsevier, 2011)
Objective: To report the outcome of partial external mitral annuloplasty in dogs with congestive heart failure (CHF) due to mitral regurgitation caused by myxomatous mitral valve degeneration (MMVD). Animals, materials and methods: Nine client-owned dogs with CHF due to mitral regurgitation caused by MMVD. Surgery consisted of a double row of pledget-butressed continuous suture lines placed into the left ventricle parallel and just ventral to the atrioventricular groove between the subsinuosal branch of the left circumflex coronary artery and the paraconal branch of the left coronary artery. Results: Two dogs died during surgery because of severe hemorrhage. Two dogs died 12 and 36 h after surgery because of acute myocardial infarction. Three dogs were euthanized 2 and 4 weeks after surgery because of progression of CHF, 1 was euthanized 30 days after surgery for non-cardiac disease, and 1 survived for 48 months. In the 5 dogs that survived to discharge there was no significant change in the left atrium to aortic ratio with surgery (3.6 ± 0.56 before surgery; 3.1 ± 0.4 after surgery; p = 0.182), and no significant change in mitral regurgitant fraction in 4 dogs in which this measurement was made (78.7 ± 2.0% before surgery; 68.7 ± 7.5% after surgery; p = 0.09). Conclusions: Partial external mitral annuloplasty in dogs with CHF due to MMVD was associated with high perioperative mortality and most dogs that survived to discharge failed to show clinically relevant palliation from this procedure. Consequently, partial external mitral annuloplasty is not a viable option for dogs with mitral regurgitation due to MMVD that has progressed to the stage of CHF. © 2011 Elsevier B.V. All rights reserved.
Keywords: Annuloplasty; Dogs; Mitral valve disease; Surgery; acute heart infarction; congestive heart failure; coronary artery circumflex branch; dog; female; left coronary artery; male; mitral annuloplasty; mitral valve disease; mitral valve regurgitation; nonhuman; perioperative period; postoperative hemorrhage; priority journal; surgical mortality; treatment outcome; Animals; Dog Diseases; Female; Heart Failure; Male; Mitral Valve Annuloplasty; Mitral Valve Insufficiency; Animalia; Canis familiaris